Nosocomial outbreak of Pantoea agglomerans in a pediatric urgent care center - Bicudo,Eliana L. (2007)
Pantoea agglomerans is a Gram-negative bacterium whose isolates can be found in blood cultures and other secretions. This article described one outbreak of sepsis due to this bacterium in the pediatric urgent care center of a tertiary hospital, in Brasilia, Federal District. This was a case-control study and it evaluated the risk factors for acquisition of nosocomial sepsis caused by Pantoea agglomerans. Six case-patients and 15 control-patients have been found. The risk factors were: vomiting in the internment and presence of solution compositions in the intravenous hydration therapy received in bigger number than 2 compositions. The transference tube used for the compositions was contaminated with Pantoea agglomerans, characterizing the outbreak with common source. The evolution of all the patients was favorable.